A guideline for the profiling of innovation bundles - Minh, Thai Thi; Michalscheck, M.; Singh, Radhika; Schmitter, Petra S. (CGIAR Initiative on Rethinking Food Markets, 2022)
Innovation bundles enable different innovations to complement one another and adapt to new contexts they are being introduced. The scalability of a bundle is measured by its ability to adapt to the context in which it is being scaled, respond positively to any system changes, and bring about intended outcomes. Profiling innovation bundles helps to assess the scalability of an innovation bundle to design the best-fit scaling strategies. Innovation bundle profiling includes but is not limited to 1) characterizing the innovation bundle, 2) assessing and enhancing the bundle’s scalability and identifying partnerships to scale the bundle, 3) providing foundation and inputs to design the scaling actions and learning and synergies across work packages, and 4) enhancing reflexivity of the intervention process to ensure that the bundling innovation is participatory, that there are ambassadors of the innovation bundling process, and that financial and human resources are dedicated to the scaling process.